Pengembangan Nilai-Nilai Keislaman di Bali pada Era Digital - Imam Muhayat; Sudarsono (Proceeding of International Conference on Islamic Boarding School, 2025)
The development of Islamic values ​​as well as the formulation of the concept of the Muslims should the ideal form of implementation in the form of expression for the enrichment of the f cognitive development , affective , and psychomotoric development as more prospective life, in order to achieve formulations form the next generation and muslim communities were friendly and ready to face the global era of digital-based. Implementation of the majesty and greatness of normative values, insaniyah , naturally values became measuring people, Bali Muslim, it can even be used as a mirror clear programmed and sustainable communities. Implications of the digital age with rapid change, the existence of aqidah, belief remains as a way of thinking, way of Investigating, a body of knowledge , and the method of high- order thinking. So that the existence of Islamic values ​​ always be able to form a spiritual and social maturity of wisdom, goodness, and informative instruments for the all muslim communities. The implications of the the development of Islamic values ​​by side with universalism values ​​for the Muslim communities woke dynamically Bali communities. So that Muslims communities can be entered at any time until the global digital era without uprooted from Islamic norms grandeur and sublime cultural values ​​are maintained.